Evaluation of the Suprafascial Thin ALT Flap in Foot and Ankle Reconstruction - Thiele, J.R.; Weiß, J.; Braig, D.; Zeller, J.; Stark, G.B.; Eisenhardt, S.U. (Journal of Reconstructive Microsurgery, 2021)
Background Distal lower extremity reconstruction can be challenging in terms of flap design. Bulky flaps result in limited mobility accompanied with the need of customized footwear. Raising the ALT-flap in a superficial fascial plane (thin ALT-flap) can be beneficial. This study evaluates thin ALT-flaps for lower distal extremity reconstruction.Methods In a retrospective study, patients that underwent microvascular extremity reconstruction at the level of the ankle and dorsal foot at the University of Freiburg from 2008–2018 were reviewed.Results 95 patients could be included in the study (35 perforator flaps, 8 fascia flaps and 54 muscle flaps).Among the perforator flaps, 21 ALT-flaps were elevated conventionally and 14 in the superficial fascial plane (thin ALT-flap). Among the conventional ALT-flaps, there was one flap loss (5%) and one successful revision (5%). 5(24%) flaps received secondary thinning. 57%(n = 12) were able to wear conventional footwear. There were 2(15%) successful revisions of thin ALT-flaps. 100% of thin ALT-flaps survived and 85%(n = 11) of the patients wore ordinary footwear after defect coverage.Among fascial flaps, 50%(n = 4) had to be revised with 2(25%) complete and 1 (13%) partial flap loss. All patients achieved mobility in ordinary shoes (n = 8).In muscle flaps, there were 7(13%) revisions and 5(9%) flap losses. 5(9%) flaps received secondary thinning. Only 33%(n = 18) were mobile in ordinary footwear.Conclusion The thin ALT-flap is a save one-stage evolution for lower distal extremity reconstruction with a favorable flap survival rate. Compared with conventional ALT-flaps it might be beneficial in reducing the need for expensive custom fitted shoes and secondary thinning procedures.
Keywords: lower limb reconstruction; thin ALT-flap; flap thinning